Analisis Strategi Pemasaran Azolla Frozen Food Bojonegoro Dalam Perspektif Etika Bisnis Islam - Abidin, Muhammad Zaenal (Maisyatuna, 2023)
During the pandemic, people's spending on groceries has increased, both in the form of raw and ready-to-eat ingredient, included shoppong frozen food. This study aims to analyze the frozen food marketing strategy at the Azolla Frozen Food Bojonegoro Store in the perspective of Islamic Business Ethics. This research is a field research (field research) with a qualitative approach. The sources of informants in this study were the owners and employees of Azolla Frozen Food. The data analysis method applied is data reduction, data presentation and conclusion. The results showed that the marketing strategy for Azolla Frozen Food generally consisted of four types, namely product strategy, price strategy, promotion strategy and distribution strategy which aimed to increase sales and profits. In the context of Islamic Business Ethics, Azolla Frozen Food's marketing strategy is based on Islamic principles. The attitude of Islamic business ethics that underlies this marketing strategy is honesty, trust, deep understanding and conveying the true information only.